A simple preparation of low water-soluble crosslinking starch-based foam containing palm oil: Thermo-physicochemical properties. (July 2022) - Wongpreedee, Thapanee; Panrot, Thidatip; Rojruthai, Porntip; Prapruddivongs, Chana
A simple preparation method was established for a low water-soluble citric acid crosslinking starch-based foam containing palm oil. The method was performed by pouring the boiling citric acid solution into the starch compound unlike the citric acid starch crosslinking by conventional solution casting. Thermo-physicochemical properties of the starch-based foams were examined. The I3300 /I1149 intensity ratio of non-citric acid-containing foam was higher, suggesting greater amounts of the available -OH groups. The addition of citric acid into the starch matrix exhibited weaker thermal stability that was attributed to the lower thermal stability of the substituted ester bonds. The increment of citric acid concentration increased thermoplastic starch foams densities as well as their cell wall thickness. No differences in moisture absorption behavior were observed after soaking in water, the non-citric acid-filled foam exhibited dissolution and changed from its original shape upon drying. Experimental results showed a promising alternative methodology to prepare low water-soluble citric acid crosslinked starch-based foam to replace conventional solution casting.